Enriched Environment Significantly Reduced Senile Plaques in a Transgenic Mice Model of Alzheimer’s Disease, Improving Memory - Balthazar, Janaina; Schöwe, Natalia Mendes; Cipolli, Gabriela Cabett; Buck, Hudson Sousa; Viel, Tania Araujo (Frontiers in Aging Neuroscience, 2018)
Alzheimer’s disease (AD) is associated with a progressive dementia, and there is good evidence that it is more pronounced in individuals that have fewer stimuli during their lives. Environmental stimulation promotes morphological and functional changes in the brain, leading to amplification of cognitive functions, and has been described in humans and animals. In this study, we evaluated the effects of enriched environment (EE) stimulation on spatial memory and senile plaque formation in transgenic mice PDGFB-APPSwInd (TG) that overexpress the human amyloid precursor protein, normally resulting in an increased density of senile plaques. We compared this group of EE stimulated transgenic mice (TG-EE) with an EE stimulated control group of age-matched C57Bl/6 wild type animals (WT-EE). Both groups were exposed to EE stimulation between the ages of 8 and 12 months. As controls of the experiment, there were a group of TG mice not exposed to EE (TG-Ctrl) and a group of WT mice not exposed to EE (WT-Ctrl). The TG-EE group presented improved spatial memory when compared to the TG-Ctrl animals. In addition, the TG-EE group showed a 69.2% reduction in the total density of senile plaques in the hippocampus when compared to the TG-Ctrl group. In this group, the concentration of senile plaques was greater in the dorsal part of the hippocampus, which is linked to spatial localization, and the reduction of this density after the submission to EE was as high as 85.1%. EE stimulation had no effect on the density of Aβ oligomers. However, amyloid scavenger receptor class B member 1 (SR-B1) density was significantly decreased in the TG-Ctrl mice, but not in the TG-EE mice, suggesting that cognitive stimulation had an effect on the formation of a cognitive reserve that could prevent the accumulation of senile plaques. It is suggested that the stimulation of old mice by EE for four months led to the formation of brain resilience that protected the brain from the deposition of senile plaques, one of the hallmarks of Alzheimer's disease, leading to improves in spatial memory.